Low-density lipoprotein cholesterol <50 mg/dL is an appropriate target after acute coronary syndrome: propensity score-matched analysis of the ODYSSEY OUTCOMES trial. (25th November 2020) - Schwartz, G.G; Szarek, M; Bhatt, D.L; Bittner, V.A; Diaz, R; Goodman, S.G; Harrington, R.A; Jukema, J.W; Kim, Y.U; Li, Q.H; Manvelian, G; White, H.D; et al.
Abstract: Background: New ESC/EAS guidelines advise a low-density lipoprotein cholesterol (LDL-C) target level <55 mg/dL for patients with acute coronary syndromes (ACS), and a level <40 mg/dL for those with recurrent events. Previous analyses of clinical trials have sought to define an optimal LDL-C target range to prevent major adverse cardiovascular events (MACE). However, those analyses are limited because patients who achieve lower versus higher LDL-C levels on lipid-lowering therapy differ in other characteristics that are prognostic for MACE, including baseline LDL-C, lipoprotein(a), and medication adherence. Aim: To overcome these limitations, we performed a propensity score-matching (PSM) analysis of the ODYSSEY OUTCOMES trial, which compared the PCSK9 inhibitor alirocumab with placebo in 18, 924 patients with recent ACS. Methods: Patients on alirocumab were classified in 1 of 3 pre-specified categories according to Month 4 LDL-C <25 (n=3357), 25–50 (n=3692) or >50 mg/dL (n=2197). Within each category, MACE after Month 4 was compared with patients on placebo using 1:1 PSM on demographic, clinical, and adherence variables. Because the trial design involved blinded substitution of placebo for alirocumab when consecutive LDL-C levels were <15 mg/dL on alirocumab, we also evaluated MACE in those patients (n=730) in comparison with patients chosen from the placebo group by 1:3 PSM. Results: Patients in the three achieved LDL-C categories of the alirocumab group differed by baseline age, sex, geographic region; history of diabetes, smoking, peripheral artery disease, cerebrovascular disease, coronary revascularization, heart failure, obstructive pulmonary disease, or malignancy; type of index ACS event; baseline LDL-C, lipoprotein(a), estimated glomerular filtration rate, body mass index, systolic blood pressure; use of intensive statin therapy; and adherence with study medication. After PSM, patients in each LDL-C category on alirocumab were well matched to patients on placebo for these characteristics. Treatment hazard ratios (HRs) for MACE (Figure) were similar in those with achieved LDL-C <25 mg/dL or 25–50 mg/dL. Patients with achieved LDL-C >50 mg/dL achieved less benefit. Patients who achieved consecutive LDL-C levels <15 mg/dL and were switched to placebo nonetheless had a robust HR (0.71, 95% CI 0.52–0.98) and thus did not dilute efficacy of alirocumab among those in the <25 mg/dL achieved LDL-C category. Conclusion: After accounting for differences in baseline characteristics and adherence, reduction in risk of MACE with alirocumab was similar in patients who achieved LDL-C <25 or 25–50 mg/dL. These data suggest that an LDL-C target of less than 50 mg/dL may be reasonable after ACS and is essentially congruent with new ESC/EAS guidelines. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Sanofi and Regeneron Pharmaceuticals, Inc